Role of transcutaneous electrical nerve stimulation in temporomandibular joint disorders - Fatima, Syeda Mahnoor; Tooba Zahoor; Ramsha Nawaz; Ahmed Tanveer; Syeda Soveba Zaidi; admin (Journal of the Pakistan Medical Association, 2024)
Objective: To compare the efficacy of transcutaneous electrical nerve stimulation with commercially available analgesics in alleviating symptoms of temporomandibular disorders. Method: The cross-sectional, interventional study was conducted from March 11, 2020, to August 31, 2023, at the Oral and Maxillofacial Surgery Department of the Armed Forces Institute of Dentistry, Rawalpindi, Pakistan, and comprised patients aged 18-65 years who were experiencing pain or distress in the temporomandibular joint region. The participants were divided into intervention group A and control group B. Group A treatment involved applying electrodes near the temporomandibular joint, with parameters adjusted as per the treatment guidelines. Group B subjects received only analgesics along with basic care recommendations. Pain intensity was assessed using visual analogue scale, while functional impairment and adverse effects were monitored. Data was analysed using SPSS 24. Results: Of the 130 patients initially assessed, 100(77%) were included; 50(50%) in each group. In group A, there were 33(66.0%) females and 17(34.0%) males with overall mean age 42.8+10.12 years. In group B, there were 30(60%) females and 20(40%) males with overall mean age 46.98+14.09 years. Pain intensity was significantly lower in group A compared to group B post-intervention (p=0.009). Group A subjects also showed significant post-intervention improvement in terms of mouth opening compared to group B patients (p<0.05). There was no significant intergroup difference with respect to adverse effects (p>0.05). Conclusion: Transcutaneous electrical nerve stimulation was significantly more effective than commercially available analgesics in alleviating symptoms of temporomandibular disorders. Key Words: Analgesia, Electric stimulation therapy, Pain management, Temporomandibular joint disorders, Transcutaneous electric nerve stimulation.